Sustitución parcial del nitrito de sodio por extracto de apio y su influencia en la calidad de una salchicha de cerdo - Vera Zambrano, Gloria Mariela (2019)
The work was carried out in order to evaluate the effect of celery powder extract on the organoleptic, physicochemical and microbiological properties of pork sausage. It is necessary to indicate that a period of 24 hours was kept curing the meat for the conversion of the nitrate present in the vegetable to nitrite, prior to the elaboration of the product. Celery extract was incorporated as a powder, in concentrations of 0.2%, 0.4% and 0.6% in the different treatments. A DCA (completely random design) was applied in a 3 * 2 bifactorial arrangement with 3 repetitions for each treatment. Sausages were determined 48 hours after elaboration: pH, acidity and residual nitrite as physical-chemical parameters. The microorganisms evaluated showed that in all treatments (T1, T2, T3, T4, T5, T6), within the range established according to the INEN NTE 1338 standard allowed for each of the microorganisms studied. The microbiological quality of the pork sausage was determined by analysis of aerobic mesophiles, escherichia coli, staphylococus aureus and salmonella. The treatment that presented the best conditions in all the variables evaluated was the T6 treatment (0.6% celery extract + 70% sodium nitrite substitution).